Salvage radical cystectomy after organ preservation therapy in patients with undifferentiated bladder cancer: its place in the treatment algorithm and survival results - P. H. Yakovlev; D. A. Kliushyn (Zaporožskij Medicinskij Žurnal)
Undifferentiated bladder cancer (G4 UBC) is aggressive disease with high potential for metastatis and local recurrence. All patients have muscle invasive disease at a presentation, which requires radical cystectomy (RCE).